2017
DOI: 10.1038/s41598-017-04091-z
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctane sulfonate affects intestinal immunity against bacterial infection

Abstract: Perfluorooctane sulfonate (PFOS) is an environmental contaminant that has been manufactured to be used as surfactants and repellents in industry. Due to long half-life for clearance and degradation, PFOS is accumulative in human body and has potential threat to human health. Previous studies have shown the development and function of immune cells can be affected by PFOS. Although PFOS has a high chance of being absorbed through the oral route, whether and how PFOS affects immune cells in the gut is unknown. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 62 publications
2
21
1
Order By: Relevance
“…The authors noted increased ROS production, lipid peroxidation, glutathione depletion, activation of caspase‐3, as well as damage to cell organelles such as mitochondria and lysosomes. Suo et al. () showed that PFOS increased IL‐22 excretion by lamina proprial lymphocytes isolated from the large intestines of wild‐type mice. This effect was not observed using F1 mice from an AhRf/f and a RORc‐cre cross to specifically delete the Ah receptor and it was concluded that this response must be dependent on the Ah receptor. Lee et al.…”
Section: Assessmentmentioning
confidence: 99%
“…The authors noted increased ROS production, lipid peroxidation, glutathione depletion, activation of caspase‐3, as well as damage to cell organelles such as mitochondria and lysosomes. Suo et al. () showed that PFOS increased IL‐22 excretion by lamina proprial lymphocytes isolated from the large intestines of wild‐type mice. This effect was not observed using F1 mice from an AhRf/f and a RORc‐cre cross to specifically delete the Ah receptor and it was concluded that this response must be dependent on the Ah receptor. Lee et al.…”
Section: Assessmentmentioning
confidence: 99%
“…In wild bottlenose dolphins, a positive correlation was demonstrated between plasma levels of PFOS and PFOA with clinical parameters of inflammation ( Fair et al, 2013 ). Futher, PFOS elevated inflammatory cytokines expression and reduced mucin production in a bacterial infection mice model ( Suo et al, 2017 ). TNF-α and IL-6, two markers of inflammation, were reportedly modulated by PFOS exposure in vivo and in vitro studies ( Han et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Suo et al, exposed mice to much higher levels of PFOS (2 mg/kg/day) and examined the response to Citrobacter rodentium (CR) infection, and found enhanced early response to CR, but eventual delayed clearance of bacteria 39 . However, these high levels of PFOS exposure may have other effects as discussed previously.…”
Section: Little Work Has Been Done Exploring the Effects Of Pfos On Rmentioning
confidence: 99%